2020
DOI: 10.3390/coatings10010080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr Target Current on the Mechanical and Tribological Performance of MoS2–Zr Composite Lubricating Coatings

Abstract: To improve the tribological properties of pure MoS2 coating, the MoS2–Zr composite lubricating coatings were prepared on the WC/TiC/Co carbide surface utilizing radio frequency magnetron sputtering method combining with multiple arc ion plating technology. The effects of different Zr target currents on the surface morphologies, roughness, Zr content, adhesive force, thickness, microhardness and tribological behaviors of the composite coatings were systematically investigated. Results showed that the properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The test results also revealed that the addition of metals (Ti, Cr, Zr, etc.) into the MoS 2 coating, to prepare the MoS 2 /metal coatings, can result in the amorphous microstructure of MoS 2 [ 21 , 22 , 23 , 26 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results also revealed that the addition of metals (Ti, Cr, Zr, etc.) into the MoS 2 coating, to prepare the MoS 2 /metal coatings, can result in the amorphous microstructure of MoS 2 [ 21 , 22 , 23 , 26 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous results, MoS 2 /Zr coatings are beneficial to improve the friction and wear properties of cemented carbide in friction tests [ 26 , 27 ] and dry cutting tests [ 28 , 29 ]. In addition, the influences of experimental conditions, such as applied force and speed, on the tribological properties have also been comprehensively researched [ 26 , 29 , 30 ]. However, the influence of deposition temperature on the performance of MoS 2 /Zr coatings and the mechanisms underlying this have not been reported in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Co-sputtering metals, non-metals, and ceramics with MoS 2 results in doped/multilayer solid lubricant lms with enhanced mechanical, lubrication, and wear resistance properties. [52][53][54][55][56] CVD is a promising method for synthesizing large area, highquality MoS 2 with layer thickness ranging from a monolayer to a few micrometers. CVD entails the vapor phase reactions of MoS 2 precursors (MoO 3 , MoCl 5 , (NH 4 ) 2 MoS 4 , S powder, etc.…”
Section: Types Of Mos 2 -Based Solid Lubricant Coatingsmentioning
confidence: 99%
“…Co-sputtering metals, non-metals, and ceramics with MoS 2 results in doped/multilayer solid lubricant films with enhanced mechanical, lubrication, and wear resistance properties. 52–56…”
Section: Tribological Properties Of Mos2mentioning
confidence: 99%
“…Zhang et al [8] and Hosseinabadi et al [9] reported a series of analyses on the rough surface of multiscale structures by calculating their fractal dimensions. Lawrence et al [10] reported the fractal characterisation of automotive cylinder linear surfaces, and some researchers [11][12][13] found that the fractal characteristics of various surface morphologies could affect anisotropy and wear performance. Jing et al [14] found that the functional properties of Ga-doped ZnO thin films could be evaluated by fractal methods.…”
Section: Introductionmentioning
confidence: 99%